Electron transport through polyene junctions in between carbon nanotubes: An ab initio realization. (November 2015) - Chen, Yiing-Rei; Chen, Kai-Yu; Dou, Kun-Peng; Tai, Jung-Shen; Lee, Hsin-Han; Kaun, Chao-Cheng
Abstract: Using both tight-binding model and ab initio calculations, we investigate a system of polyene-bridged armchair carbon nanotube electrodes to address quantum transport through junctions with multiple conjugated molecules. Both one-polyene and two-polyene cases are considered. The ab initio results of the two-polyene cases show the interference effect in transmission and its strong dependence on the configuration of contact sites. This agrees with the tight-binding model. In addition, the discrepancy brought by ab initio relaxation provides an insight into how the junction's geometry, bonding, and effective potential influence the transmission spectra.